Hemocompatibility of Nanotitania-Nanocellulose Hybrid Materials - Fredric G. Svensson; Vivek Anand Manivel; Gulaim A. Seisenbaeva; Vadim G. Kessler; Bo Nilsson; Kristina N. Ekdahl; Karin Fromell (Nanomaterials, 2021)
In order to develop a new type of improved wound dressing, we combined the wound healing properties of nanotitania with the advantageous dressing properties of nanocellulose to create three different hybrid materials. The hemocompatibility of the synthesized hybrid materials was evaluated in an in vitro human whole blood model. To our knowledge, this is the first study of the molecular interaction between hybrid nanotitania and blood proteins. Two of the hybrid materials prepared with 3 nm colloidal titania and 10 nm hydrothermally synthesized titania induced strong coagulation and platelet activation but negligible complement activation. Hence, they have great potential as a new dressing for promoting wound healing. Unlike the other two, the third hybrid material using molecular ammonium oxo-lactato titanate as a titania source inhibited platelet consumption, TAT generation, and complement activation, apparently via lowered pH at the surface interface. It is therefore suitable for applications where a passivating surface is desired, such as drug delivery systems and extracorporeal circuits. This opens the possibility for a tailored blood response through the surface functionalization of titania.